Composite magnetic abrasive and preparation method thereof
By introducing sintering additives into the magnetic abrasive particles and reacting high temperatures with the grinding phase, and embedded on the iron matrix, the problems of short service life and high preparation cost of existing magnetic abrasive particles are solved, and more efficient and economical preparation of magnetic abrasive particles are achieved.
Patent Information
- Application Number
- CN202510001620.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing magnetic abrasive particles have short service life and high production cost.
The preparation method of composite magnetic abrasive is adopted, including an iron matrix, a binder and whisker structure generated by the reaction of the sintering additive and the grinding phase at high temperature. Through the high-temperature sintering process, the grinding phase and whisker structure are embedded on the surface of the iron matrix, improving the strength and toughness of the abrasive particles.
The service life of magnetic abrasive particles is extended, and the preparation cost is reduced, which improves the wear resistance and magnetic properties of the abrasive particles.
Smart Images

Figure CN119794334A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic abrasives, in particular to a composite magnetic abrasive and a preparation method thereof. Background Art
[0002] In the current magnetic grinding process, the grinding phase-iron matrix magnetic abrasive is commonly used. The grinding phase is commonly used such as Al2O3, TiC, SiC, etc., and the iron matrix is generally reduced iron powder. In addition, the existing magnetic abrasive production process is relatively simple, and the strength and toughness are not high, so the service life is short. For example, although Al2O3-Fe magnetic abrasive can achieve grinding of the workpiece, it cannot achieve continuous removal of the workpiece surface. After it has completed grinding the workpiece for a period of time, if you want to continue to improve the precision of the workpiece, you must stop processing and switch to other grinding abrasives, which greatly limits the grinding efficiency. In addition, the production cost of high-performance magnetic abrasives such as magnetic abrasives prepared by gas atomization rapid solidification method is too high.
[0003] Therefore, how to improve the performance of magnetic abrasive particles and reduce the preparation cost of magnetic abrasive particles is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The technical task of the present invention is to provide a composite magnetic abrasive and a preparation method thereof to solve the problem of how to improve the performance of the magnetic abrasive grains themselves and reduce the preparation cost of the magnetic abrasive grains.
[0005] The technical task of the present invention is achieved in the following manner: a composite magnetic abrasive, the composite magnetic abrasive comprising an iron matrix, a binder and a whisker structure, wherein the whisker structure is a reinforced and toughened structure generated by a reaction between a sintering additive and two grinding phases or one of the two grinding phases at high temperature;
[0006] Among them, the iron matrix is 40-60 parts, the binder is 3-5 parts, the two grinding phases are 20-40 parts, and the sintering additive is 5-10 parts.
[0007] Preferably, the particle size of the iron matrix is 150-160 μm.
[0008] Preferably, the iron matrix is one or more of reduced iron powder, spherical iron powder and carbonyl iron powder.
[0009] Preferably, the whisker structure is a thin and long structure with a size of 10-20 μm.
[0010] Preferably, the particle size ratio of the two grinding phases is 20:3-10:1, and the particle size of the grinding phase with a large particle size does not exceed 20 μm.
[0011] Preferably, the two grinding phases are aluminum oxide and silicon carbide.
[0012] Preferably, the particle size of the sintering additive is 1-3 μm;
[0013] Sintering additives include manganese, chromium or copper. At high temperatures, the two grinding phases can react with them to become hard, which has a reinforcing and toughening effect on the grinding phases. For the iron matrix, the magnetic phase distribution of the iron matrix is changed, the density of effective magnetic atoms is increased, and the saturation magnetization intensity is improved. Manganese atoms cause grain refinement and generate new magnetic phases, thereby increasing the coercive force.
[0014] More preferably, the binder is a 5% by mass polyvinyl alcohol aqueous solution.
[0015] A method for preparing a composite magnetic abrasive, the preparation method is specifically as follows:
[0016] (1) taking 20-40 parts of two grinding phases, 40-60 parts of iron matrix and 5-10 parts of sintering additives, adding 3-5 parts of 5% by weight polyvinyl alcohol aqueous solution and mixing evenly to obtain a mixed material;
[0017] (2) Taking the mixed material and pressing it into a blank, the pressure is 80-110KN;
[0018] (3) placing the blank into a drying oven for drying to obtain a dried blank; wherein the drying temperature is 100-110° C. and the drying time is 10-12 h;
[0019] (4) taking the dried blank and placing it in a sintering furnace for sintering treatment, during which the sintering additive reacts with the two grinding phases at high temperature to produce a reinforced and toughened whisker structure; wherein the sintering parameters are 1200° C.-1250° C. for 6-6.5 hours, a heating rate of 3-3.3° C. / min, and a holding time of 2-2.5 hours;
[0020] (5) After sintering, the particles are manually crushed and 150-220 μm magnetic abrasive particles are screened out.
[0021] Preferably, after the sintering treatment in step (4), during the cooling of the sintering furnace to room temperature, manganese reacts with silicon carbide to form manganese silicide whiskers; the manganese silicide whiskers are stable at high temperatures and grow in the form of whiskers; and free carbon is released when Mn reacts with silicon carbide, and the free carbon reacts with manganese at high temperatures to form manganese carbide whiskers; the manganese carbide whiskers grow through liquid phase mass transfer under a gas-liquid-solid (VLS) mechanism; the iron matrix reaches a level that it does not melt, so that the two grinding phases and the generated whisker structure can be embedded in the surface of the iron matrix.
[0022] The composite magnetic abrasive and the preparation method thereof of the present invention have the following advantages:
[0023] (i) Different from the conventional abrasive grains composed of two grinding phases, the composite magnetic abrasive of the present invention is composed of a magnetic matrix, two grinding phases, a sintering additive and a whisker structure produced by the high-temperature reaction of the grinding phase and the sintering additive. The sintering temperature is raised to a temperature higher than the melting temperature of the sintering additive and lower than the melting temperature of the magnetic matrix by a high-temperature sintering furnace. Two silicon carbide and aluminum oxide with relatively large size differences react with Mn in a high-temperature environment to produce a whisker structure. In addition, the iron matrix is melted but not melted in a high-temperature environment, so that the grinding phase and the produced whisker structure can be embedded in the surface of the iron matrix. The sintering additive Mn melts at the melting point and further strengthens the two grinding phases embedded in the iron matrix surface. The two grinding phases and the produced whisker structure further improve the strength and toughness of the magnetic abrasive grains, improve their wear resistance, extend the service life of the magnetic abrasive grains, and greatly reduce the production cost;
[0024] (ii) The composite magnetic abrasive processing of the present invention not only enhances the strength and toughness of the magnetic abrasive grains to achieve the purpose of extending the service life of the magnetic abrasive grains, but also reduces the preparation cost of the magnetic abrasive grains;
[0025] (iii) The grinding phase on the outer surface of the abrasive grains of the present invention comprises multiple layers, the inner matrix of the composite magnetic abrasive grains is an iron matrix, the outer layer of the iron matrix is inlaid with two grinding phases and a sintering additive after condensation, and a whisker structure generated by the grinding phases and the sintering additives during high-temperature sintering; at the same time, the sizes of the two grinding phases are relatively different, the purpose is to facilitate the fixing and inlaying of the grinding phases with each other, and further improve the service life of the magnetic abrasive grains;
[0026] (iv) The sintering additives of the present invention are manganese, chromium, copper, etc., which can react with the grinding phase and have a melting point below the sintering temperature, so as to further fix the grinding phase and the iron matrix;
[0027] (V) The present invention utilizes a high-temperature sintering furnace to raise the sintering temperature to a temperature higher than the melting point of the sintering additive and lower than the melting temperature of the magnetic matrix, embeds the two grinding phases into the surface of the magnetic matrix, and reacts the grinding phases and the sintering additives through a high-temperature reaction to produce a reinforced and toughened whisker structure, thereby increasing the strength and toughness of the magnetic abrasive grains and improving their wear resistance, thereby extending the service life of the magnetic abrasive grains. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention is further described below in conjunction with the accompanying drawings.
[0029] Attached Figure 1 Microscopic SEM and EDS images of composite magnetic abrasive containing Mn additives;
[0030] Attached Figure 2 Enlarged SEM and EDS images of composite magnetic abrasive whiskers containing additive Mn;
[0031] Attached Figure 3This is a schematic diagram of the structure of SiC / Fe magnetic abrasive purchased on the market;
[0032] Attached Figure 4 is the hysteresis curve of magnetic abrasive particles. DETAILED DESCRIPTION
[0033] The composite magnetic abrasive and its preparation method of the present invention are described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] Embodiment 1:
[0035] This embodiment provides a composite magnetic abrasive, which includes an iron matrix, a binder and a whisker structure, wherein the whisker structure is a reinforced and toughened structure generated by a reaction between a sintering additive and two abrasive phases or one of the two abrasive phases at high temperature;
[0036] Among them, the iron matrix accounts for 50% by mass in the composite magnetic abrasive; the binder accounts for 5% by mass in the composite magnetic abrasive; the two grinding phases account for 36% by mass in the composite magnetic abrasive; the sintering additive accounts for 9% by mass in the composite magnetic abrasive; the binder acts as a forming agent and is discharged during the sintering process.
[0037] The particle size of the iron matrix in this embodiment is 150-160 μm.
[0038] The iron matrix in this embodiment is one or more of reduced iron powder, spherical iron powder, and carbonyl iron powder.
[0039] The whisker structure in this embodiment is a thin and long structure with a size of 10-20 μm.
[0040] The particle size ratio of the two grinding phases in this embodiment is 20:3-10:1, and the particle size of the grinding phase with a large particle size does not exceed 20 μm.
[0041] The two grinding phases in this embodiment are aluminum oxide and silicon carbide.
[0042] The particle size of the sintering additive in this embodiment is 1-3 μm;
[0043] Sintering additives include manganese, chromium or copper. At high temperatures, the two grinding phases can react with them to become hard, which has a reinforcing and toughening effect on the grinding phases. For the iron matrix, the magnetic phase distribution of the iron matrix is changed, the density of effective magnetic atoms is increased, and the saturation magnetization intensity is improved. Manganese atoms cause grain refinement and generate new magnetic phases, thereby increasing the coercive force.
[0044] The binder in this embodiment is a polyvinyl alcohol aqueous solution with a mass fraction of 5%.
[0045] Example 2 (SiC / Al2O3 / Fe composite magnetic abrasive containing Mn additive)
[0046] This embodiment provides a method for preparing a composite magnetic abrasive, and the preparation method is specifically as follows:
[0047] (1) Material preparation: 60 g of Fe powder with a particle size of 150 μm; 10 g of Al2O3 powder with a particle size of 10 μm-20 μm; 20 g of SiC powder with a particle size of 3 μm-1 μm, and 10 g of Mn powder with an average particle size of 1 μm-3 μm;
[0048] (2) Pressing abrasives into blanks: Fe powder, Al2O3, SiC and Mn were mixed to a certain degree, and then 3g of polyvinyl alcohol aqueous solution was added to mix evenly, and the mixture was put into a pressing machine and pressed into blanks at a pressing force of 110KN;
[0049] (3) Drying: After pressing, place in a vacuum drying oven at 1120°C for 12 hours;
[0050] (4) Sintering: The blank is placed in a vacuum sintering furnace and sintered at 1200°C for 6 hours, with a heating rate of 3.3°C / min and a holding time of 2.5 hours; then it is cooled to room temperature with the furnace. During this process, Mn reacts with silicon carbide (SiC) to form manganese silicide whiskers (MnSi); these silicides are stable at high temperatures and grow in the form of whiskers; and Mn reacts with silicon carbide (SiC) to release free carbon (C), which reacts with Mn at high temperatures to form manganese carbide whiskers (Mn2C). The whiskers grow through liquid phase mass transfer under the gas-liquid-solid (VLS) mechanism; the iron matrix reaches a level where it cannot be melted, so that the two grinding phases and the resulting whisker structure can be embedded in the surface of the iron matrix;
[0051] (5) Crushing: The sintered blank is first crushed into a suitable size manually and then the required composite magnetic abrasive is screened out with a sieve.
[0052] Example 3 (SiC / Al2O3 / Fe composite magnetic abrasive grains without sintering agent)
[0053] (1) Material preparation: 55 g of Fe powder with a particle size of 150 μm; 20 g of Al2O3 powder with a particle size of 10 μm; and 20 g of SiC powder with a particle size of 1 μm.
[0054] (2) Pressing abrasives into blanks: Fe powder, Al2O3 and SiC are mixed to a certain degree, and then 4g of polyvinyl alcohol aqueous solution is added to mix evenly, and the mixture is put into a pressing machine and pressed into blanks at a pressing force of 110KN;
[0055] (3) Drying: After pressing, place in a vacuum drying oven at 1120°C for 12 hours;
[0056] (4) Sintering: The blank was placed in a vacuum sintering furnace and sintered at 1200°C for 6 hours, with a heating rate of 3.3°C / min and a holding time of 2.5 hours; then cooled to room temperature in the furnace;
[0057] (5) Crushing: The sintered blank is first crushed into a suitable size manually and then the required composite magnetic abrasive is screened out with a sieve.
[0058] Example 4 (SiC / Fe composite magnetic abrasive)
[0059] (1) Material preparation: Fe powder 55 with a particle size of 150 μm; SiC powder 48 with a particle size of 10 μm
[0060] (2) Pressing the abrasive into a blank: After mixing Fe powder and SiC to a certain degree, add 4.5 ethylene alcohol aqueous solution and mix evenly, put it into a pressing machine and press it into a blank with a pressing force of 110KN;
[0061] (3) Drying: After pressing, place in a vacuum drying oven at 120°C for 12 hours;
[0062] (4) Sintering: The blank was placed in a vacuum sintering furnace and sintered at 1150°C for 6 hours, with a heating rate of 3.2°C / min and a holding time of 3 hours; then cooled to room temperature in the furnace;
[0063] (5) Crushing: The sintered blank is first crushed into a suitable size manually and then the required composite magnetic abrasive is screened out with a sieve.
[0064] Example 5 (Al2O3 / Fe magnetic abrasive)
[0065] (1) Material preparation: 50 g of Fe powder with a particle size of 150 μm; 45 g of Al2O3 powder with a particle size of 10 μm;
[0066] (2) Pressing the abrasive into a blank: After mixing Fe powder and Al2O3 to a certain degree, add 3.5g of polyvinyl alcohol aqueous solution and mix evenly, put it into a pressing machine and press it into a blank at a pressing force of 110KN;
[0067] (3) Drying: After pressing, place in a vacuum drying oven at 120°C for 12 hours;
[0068] (4) Sintering: The blank was placed in a vacuum sintering furnace and sintered at 1150°C for 6 hours, with a heating rate of 3.2°C / min and a holding time of 3 hours; then cooled to room temperature in the furnace;
[0069] (5) Crushing: The sintered blank is first crushed into a suitable size manually and then the required composite magnetic abrasive is screened out with a sieve.
[0070] The structure of the composite magnetic abrasive material for completely fine machining proposed in this embodiment is as shown in the attached Figure 1 As shown, it can be seen that there are two grinding phases, the sizes of the two grinding phases are quite different, relatively small silicon carbide particles are attached to the spherical alumina, and whiskers are generated on the surface of the iron matrix, which can achieve long-term and efficient grinding. Figure 2 This is the EDS image of the whisker structure. It can be seen that the main components of the whiskers are Mn and Si.
[0071] The structure of existing magnetic abrasive is as follows Figure 3 As shown, it can be seen that there is only one grinding phase. When the grinding phase fails, the life of this magnetic abrasive is exhausted, and long-term grinding cannot be achieved. In addition, the preparation cost is high, and the uniform spherical structure is not formed, so precision grinding cannot be achieved.
[0072] Attached Figure 4 For the hysteresis curve of this composite magnetic abrasive, Figure 3 The hysteresis curve can be used to read the saturation magnetization and coercive force of the composite magnetic abrasive.
[0073] The performance of magnetic abrasive grains is mainly judged by two indicators: saturation magnetization Ms and coercive force Hc. The saturation magnetization is the maximum magnetization that can be achieved when magnetic abrasive grains are magnetized in an external magnetic field. The greater the saturation magnetization of magnetic abrasive grains, the stronger the magnetic field induction sensitivity, the faster the magnetization speed, the higher the relative magnetic permeability, the better the ferromagnetic properties, and the stronger the grinding pressure and the ability to agglomerate with each other applied by the magnetic abrasive grains to the workpiece during operation. After the magnetic abrasive grains are saturated magnetized, when the external magnetic field returns to zero, the magnetic induction intensity of the magnetic abrasive grains cannot return to zero. A certain magnetic field must be applied in the opposite direction of the external magnetic field to return the magnetic induction intensity to zero. The applied magnetic field is called coercive force. Therefore, magnetic abrasive grains with larger saturation magnetization and smaller coercive force are preferred in magnetic grain grinding and finishing technology. Table 1 is a comparison of the saturation magnetization and coercive force of Examples 2 to 5 and SiC / Fe magnetic abrasive grains purchased on the market.
[0074] Table 1
[0075]
[0076] As can be seen from Table 1, in this embodiment, based on the sintering additive, the two abrasive phases react at high temperature to produce whisker structure and the melting point of the sintering additive is reached during sintering so that the two abrasive phases are combined together through the molten sintering additive. After cooling, the sintering additive also solidifies to make the combination more firm, further enhancing its performance and reducing the cost of preparing high-performance magnetic abrasives.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite magnetic abrasive, characterized in that: The composite magnetic abrasive comprises an iron matrix, a binder and a whisker structure, wherein the whisker structure is a reinforced and toughened structure generated by the reaction of a sintering additive and two grinding phases or one of the two grinding phases at high temperature; Among them, the iron matrix is 40-60 parts, the binder is 3-5 parts, the two grinding phases are 20-40 parts, and the sintering additive is 5-10 parts.
2. The composite magnetic abrasive according to claim 1, characterized in that: The particle size of the iron matrix is 150-160 μm.
3. The composite magnetic abrasive according to claim 1, characterized in that: The iron matrix is one or more of reduced iron powder, spherical iron powder and carbonyl iron powder.
4. The composite magnetic abrasive according to claim 1, characterized in that: The whisker structure is a thin and long structure with a size of 10-20 μm.
5. The composite magnetic abrasive method according to claim 1, characterized in that: The particle size ratio of the two grinding phases is 20:3-10:1, and the particle size of the grinding phase with a large particle size does not exceed 20 μm.
6. The composite magnetic abrasive according to claim 1, characterized in that: The two grinding phases are aluminum oxide and silicon carbide.
7. The composite magnetic abrasive according to claim 1, characterized in that: The particle size of the sintering additive is 1-3 μm; Sintering additives include manganese, chromium or copper.
8. The composite magnetic abrasive according to any one of claims 1 to 7, characterized in that: The binder is a 5% by mass polyvinyl alcohol aqueous solution.
9. A method for preparing a composite magnetic abrasive, characterized in that: The preparation method is specifically as follows: (1) taking 20-40 parts of two grinding phases, 40-60 parts of iron matrix and 5-10 parts of sintering additives, adding 3-5 parts of 5% by weight polyvinyl alcohol aqueous solution and mixing evenly to obtain a mixed material; (2) Taking the mixed material and pressing it into a blank, the pressure is 80-110KN; (3) placing the blank into a drying oven for drying to obtain a dried blank; wherein the drying temperature is 100-110° C. and the drying time is 10-12 h; (4) taking the dried blank and placing it in a sintering furnace for sintering treatment, during which the sintering additive reacts with the two grinding phases at high temperature to produce a reinforced and toughened whisker structure; wherein the sintering parameters are 1200° C.-1250° C. for 6-6.5 hours, a heating rate of 3-3.3° C. / min, and a holding time of 2-2.5 hours; (5) After sintering, the particles are manually crushed and 150-220 μm magnetic abrasive particles are screened out.
10. The method for preparing the composite magnetic abrasive according to claim 9, characterized in that: After the sintering treatment in step (4), when the sintering furnace is cooled to room temperature, manganese reacts with silicon carbide to form manganese silicide whiskers; the manganese silicide whiskers are stable at high temperatures and grow in the form of whiskers; and free carbon is released when Mn reacts with silicon carbide, and the free carbon reacts with manganese at high temperatures to form manganese carbide whiskers; the manganese carbide whiskers grow through liquid phase mass transfer under a gas-liquid-solid mechanism; the iron matrix reaches a level that it does not melt, so that the two grinding phases and the generated whisker structure can be embedded in the surface of the iron matrix.
Citation Information
Patent Citations
Electroplated super abrasive tools with the abrasive particles chemically bonded and deliberately placed, and methods for making the same
CA2773197A1
Toughened sintering auxiliary agent used for normal-pressure sintering of boron carbide ceramic and preparation method for toughened sintering auxiliary agent
CN107973608A
Magnetizable abrasive particles and method of making same
CN114026660A
Bonding method magnetic grinding material with adjustable self-sharpening performance and preparation method of bonding method magnetic grinding material
CN115785906A
Hot pressing sintering process of preparing magnetic abrasive
CN1297976A